ANALISIS EFEK MODERASI TINGKAT PELAYANAN PADA PENGARUH PRODUK DAN HARGA TERHADAP KEPUTUSAN MEMBELI (Survei pada Konsumen Luwes Group Surakarta) - Widajanti, Erni (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
This research aimed to analyze the effect of the product and the price of thepurchase decision with the level of service as a moderating variable (Survey onconsumer Luwes group Surakata). The population in this study is that consumersLuwes Group Surakarta. While the sample is taken as many as 50 people withpurposive random sampling method.The results of the research indicate thatregression test showed that the variable regression dominant influence on consumerdecision in buying products in Luwes Group is the price. T test results showed that:1. There was a significant effect of the product on the consumer's decision to buyLuwes Group Surakarta, so hypothesis 1 proved to be true. 2. There is a significantinfluence on the price of consumer buying decisions on consumer Luwes GroupSurakarta, so hypothesis 2 unsubstantiated. 3. There is no significant effect of thelevel of service to the consumer buying decision on Luwes Group Surakarta., Thethird hypothesis is not proven true. This absolute difference I in test results showthat: the level of service does not moderate influence on the decision to buy theproduct on Luwes group Surakarta. So the hypothesis 4 is not proven true. The testresults showed that the difference in absolute II: the level of service moderate theeffect of price on purchase decisions on Luwes group Surakarta, so the hypothesis 5proven true.Keywords: product, price, service level, the decision to buy.